Standardized Weaning from Temporary Extracorporeal Life Support in Cardiovascular Patients - Thomas, Marie; Kreibich, Maximilian; Beyersdorf, Friedhelm; Benk, Christoph; Maier, Sven; Trummer, Georg (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives Separation from extracorporeal life support (ECLS) is often based on individual decisions rather than evaluated standard operating procedures (SOPs). Therefore, we strived to evaluate a SOP, summarizing specific treatment paths for this group of patients.Methods A total of 107 cardiovascular patients were supported with ECLS within a 4-year period. Fifty-three patients were treated before the SOP was introduced (group A) and 54 patients were treated afterward (group B). Patient characteristics and outcomes were analyzed and compared between the two time periods regarding baseline characteristics, compliance with SOP criteria, and the end points successful weaning and 30-day survival.Results Successful weaning rose significantly from 56.6 to 74.1% (p = 0.045) and 30-day survival rate increased from 34.0 to 50.0% (p = 0.069) after implementation of the SOP. Successful weaning was significantly associated with daily echocardiography (p = 0.012) and circulatory support with dobutamine (p = 0.026). The investigated other criteria used in the weaning process did not show a significant correlation with better outcome.Conclusion The SOP for ECLS weaning showed higher weaning rates compared with a weaning based on individual decisions. Although only parts of the SOP were associated with higher weaning and survival rates, the SOP was experienced as a useful guideline for standardized ECLS management.
Keywords: mechanical circulatory support; extracorporeal life support; ECLS; postcardiotomy failure; extracorporeal membrane oxygenation; weaning protocol